High Circulating Sclerostin is Present in Patients with Thalassemia-associated Osteoporosis and Correlates with Bone Mineral Density - Voskaridou, E.; Christoulas, D.; Plata, E.; Bratengeier, C.; Anastasilakis, A.; Komninaka, V.; Kaliontzi, D.; Gkotzamanidou, M.; Polyzos, S. A.; Dimopoulou, M.; Terpos, E. (Hormone and Metabolic Research, 2012)
Osteoporosis is a severe complication of thalassemia. Sclerostin is a Wnt signaling inhibitor, which is produced by osteocytes and inhibits osteoblast function. Sclerostin is implicated in the pathogenesis of osteoporosis of different etiology. The aim of the study was to evaluate circulating sclerostin in 66 patients (median age 42 years) with thalassemia and osteoporosis who participated in a phase 2, randomized study (zoledronic acid vs. placebo) and the results were compared with those of 30 healthy controls (median age 44 years) without osteopenia/osteoporosis and 62 women with postmenopausal osteoporosis (median age 63 years). At baseline, thalassemic patients with osteoporosis had elevated circulating levels of sclerostin (median: 605 pg/ml, range: 22–1 227 pg/ml) compared to healthy controls without osteopenia/osteoporosis (250 pg/ml, 0–720 pg/ml, p<0.001) and reduced levels of sclerostin compared with postmenopausal women with osteoporosis (840 pg/ml, 181–1 704 pg/ml, p<0.001). Thalassemia patients had also increased serum dickkopf-1 (Dkk-1) and high bone turnover. Circulating sclerostin levels correlated with bone mineral density in lumbar spine (r=0.619, p<0.001), distal radius (r=0.401, p=0.001) and femoral neck (r=0.301, p=0.021). Zoledronic acid did not alter sclerostin levels after 12 months of therapy, although it reduced circulating Dkk-1. We conclude that circulating sclerostin is elevated in thalassemia patients with osteoporosis and correlated with their BMD, but it was not reduced post zoledronic acid administration. These findings suggest that high sclerostin may serve as a marker of increased osteocyte activity in thalassemia patients. Drugs targeting sclerostin may also be used in this difficult to treat disorder associated with bone loss.
Keywords: thalassemia; osteoporosis; sclerostin; dickkopf-1; osteoblasts